1976
DOI: 10.1271/bbb1961.40.1011
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine decomposing enzymes in Pseudomonas putida.

Abstract: Creatinine was found to be rapidly decomposed by several strains belonging to Pseudomonas, one of which was assigned to P. putida. Analyses of the metabolites indi cated that creatinine was converted to sarcosine via creatine and further to glycine. The enzymes involving in a metabolic pathway of creatinine, i.e. creatinine amidohydrolase (EC 3.5.2), creatine amidinohydrolase (EC 3.5.3.3) and sarcosine dehydrogenase (EC 1.5.99.1), were found to be inducibly formed and accumulated in the bacterial cells. A nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This reaction is the first step of the creatinine-metabolizing pathway found in Pseudomonas putida. 1 Creatine is then degraded by creatinase (EC 3.5.3.3), 2 sarcosine dehydrogenase (EC 1.5.3.1), 3 and formaldehyde dehydrogenase (EC 1.1. 1.159) 4 in this microorganism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction is the first step of the creatinine-metabolizing pathway found in Pseudomonas putida. 1 Creatine is then degraded by creatinase (EC 3.5.3.3), 2 sarcosine dehydrogenase (EC 1.5.3.1), 3 and formaldehyde dehydrogenase (EC 1.1. 1.159) 4 in this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…1 Later, it was found that the enzyme activity was increased approximately 4-fold by the addition of manganese. 5 The gene encoding creatininase was cloned from P. putida and over-expressed using an Escherichia coli system.…”
Section: Introductionmentioning
confidence: 99%
“…Creatinine amidohydrolase is widely distributed binuclear Zn 2+ enzyme responsible for the hydrolysis of creatinine to form creatine 15,16 . Interestingly, within this family are the two subfamilies FAPy deformylase and the mycofactocin peptidase, both of which are associated with cofactor or putative cofactor biosynthesis.…”
mentioning
confidence: 99%
“…Although a peptidase is not encoded by the Mft cluster, we were intrigued by the presence of a gene that encodes a protein with similarity to the creatininase subfamily of amidohydrolases. The prototypical creatininase hydrolyzes an amide bond in the cyclic metabolite creatinine to produce creatine (23)(24)(25). We reasoned that it might be possible that the creatininase homolog encoded in this cluster potentially processes the decarboxylated MftA to a smaller metabolite en route to the mature natural product.…”
mentioning
confidence: 99%